2023
DOI: 10.3390/biomedicines11092438
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Center Real-World Outcomes of Nivolumab Plus Ipilimumab and Chemotherapy in Patients with Metastatic Non-Small-Cell Lung Cancer

Walid Shalata,
Alexander Yakobson,
Yulia Dudnik
et al.

Abstract: Immune checkpoint inhibitors have become the standard of care in the treatment of metastatic non-small-cell lung cancer (NSCLC). The combination of nivolumab plus ipilimumab and chemotherapy has been shown to improve outcomes in terms of overall survival (OS) and progression-free survival (PFS). The aim of this study was to evaluate the outcomes of metastatic NSCLC treated in routine practice on the treatment regimen of the CheckMate 9LA protocol. Medical records of 58 patients treated at Soroka and Bnai Zion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…In contrast, PD1/PDL1 inhibitors disrupt the immunosuppressive effects on anti-tumor T cells, leading to increased T cell proliferation and infiltration into the tumor microenvironment, thereby triggering an anti-tumor response. Current anti-PD1/PDL1 therapies block the interaction between PD1 and PDL1, effectively reactivating suppressed immune cells and initiating an anti-tumor immune response [13,[41][42][43][44][45][46][47][48][49][50][51][52]. The ICIs function by obstructing the inhibitory signals originating from tumor cells to the T cells that target them.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, PD1/PDL1 inhibitors disrupt the immunosuppressive effects on anti-tumor T cells, leading to increased T cell proliferation and infiltration into the tumor microenvironment, thereby triggering an anti-tumor response. Current anti-PD1/PDL1 therapies block the interaction between PD1 and PDL1, effectively reactivating suppressed immune cells and initiating an anti-tumor immune response [13,[41][42][43][44][45][46][47][48][49][50][51][52]. The ICIs function by obstructing the inhibitory signals originating from tumor cells to the T cells that target them.…”
Section: Discussionmentioning
confidence: 99%
“…It works similarly to nivolumab in that it blocks the inhibition of T cells, thus allowing them to attack tumor cells. The findings of two separate studies, CheckMate 227 and Checkmate 9LA, support nivolumab plus ipilimumab as a treatment in first-line therapy for advanced NSCLC regardless of the PD-L1 expression level [3]. The side effects of nivolumab and other immune checkpoint inhibitors are not the same as those of cytotoxic chemotherapy.…”
Section: Introductionmentioning
confidence: 95%
“…Because immune checkpoint inhibitors activate T cells, the majority of their side effects are immunologically mediated, including skin rash, pericarditis, thyroiditis, colitis, hepatitis, pneumonitis, and hypophysitis [4]. These side effects often occur within a year after starting ICI treatment [3,4]. Cardiac complications are very rare immune-related side effects of ICIs, occurring in less than 1% of patients; however, these complications have a mortality rate of up to 50% [5].…”
Section: Introductionmentioning
confidence: 99%
“…Histological analysis of a biopsy from the afflicted area may reveal inflammatory infiltrates (often T-cell-predominant lymphocytic infiltrate) in the myocardium, which are not consistent with ischemia damage from coronary artery disease. In order to increase the test's sensitivity, immunostains for cell-specific markers including T lymphocytes (CD3), macrophages (CD68), or human leukocyte antigens may be used [6,[35][36][37][38][39][40][41][42][43][44][45][46][47][48].…”
Section: Diagnosismentioning
confidence: 99%
“…Cardiac complications can lead to serious repercussions or even death, while interruptions in cancer therapy can increase the risk of disease progression. Retrospective studies have shown that patients with advanced melanoma or non-small cell lung cancer who initially responded positively to ICIs but had to discontinue treatment because of irAEs may not need to restart ICI therapy [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. The decision to rechallenge with ICI therapy following the development of ICI-associated myocarditis is complex and personalized decisions should be made through multidisciplinary discussions, taking into account the patient's cancer status, response to immunotherapy, availability of alternative effective therapy, severity of cardiotoxicity, and regression of toxic effects.…”
Section: Treatmentmentioning
confidence: 99%